Effect of Education and Knowledge on Domestic Waste Management for Housewives in Medan City in 2022 - Azrina Sufi Nasution; Sri Malem Indirawati; Nurmaini Nurmaini (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to analyze effect of education and knowledge on domestic waste management for housewives in Medan City in 2022. This type of research is an analytic survey using a cross sectional and quantitative research design. The population in this study are housewives who live in 7 Sub-Districts (Region-III) in Medan City. The sample in this study is obtained from 4 Sub-Districts in Region-III Medan City. The sampling method used in this study was purposive sampling. The selected Sub-Districts are Medan Tembung District, Medan Marelan District, Medan Deli District, and Medan Labuhan District. The distribution of samples is distributed proportionally with 25 samples in each Sub-Districts. The statistical test used in this study is logistics regression multivariate analysis. The results show that education has effect on action of domestic waste management for housewives in Medan City in 2022. Knowledge has effect on action of domestic waste management for housewives in Medan City in 2022.